Predictors of Stunting among Preschool-Aged Children in Uasin Gishu County, Kenya - Were, Gertrude M.; Kosgei , Sheila C.; Serrem, Charlotte; Osano, Odipo (African Journal of Education,Science and Technology (AJEST), 2024)
Globally, approximately 149.2 million preschoolers are stunted and about 30% of them come from Africa. An estimated one million deaths annually among preschoolers are associated with stunting. Africa and South Asia share the highest proportion of stunting with 36% and 34% respectively. In Kenya, stunting rates among preschool-aged children is at 26% which is still a public health concern. Despite Uasin Gishu County’s abundance of food from both crop and livestock farming stunting persists among preschoolers with a prevalence of 31%. This investigation aimed at assessing the child- and household-related predictors of stunting among preschoolers. A cross-sectional survey design was adopted with a sample size of 289 children. Children alongside their caregivers were selected through a three-tier sampling technique consisting of purposive, stratified and simple random sampling. Socio-demographic data was collected using researcher-administered questionnaires. Stunting data was collected using a height/length board. Data analysis was carried out using WHO Anthro Software and SPSS version 23. The findings indicated that 29.4% of preschoolers in Uasin Gishu County are stunted, with male children being stunted (33.55%) compared to female children (24.82%). Majority (46.8%) of the children aged 12-23 months were stunted. The probability of stunting was higher among children from mothers with a lower level of education (p value=0). Children from married parents and those from low-income households (p value=0.002, OR=6.55) also had lower chances of stunting. These findings underscore the multifaceted nature of stunting, which is influenced by the child’s gender, marital status, maternal education, and household wealth.